Tezosentan, an endothelin receptor antagonist, limits liver injury in endotoxin challenged cirrhotic rats. Issue 12 (11th November 2004) - Urbanowicz, W; Sogni, P; Moreau, R; Tazi, K A; Barriere, E; Poirel, O; Martin, A; Guimont, M C; Cazals-Hatem, D; Lebrec, D
Abstract : Background/aims: Lipopolysaccharide (LPS) induces liver injury which is associated with upregulated endothelin (ET)-1 production. The aim of this study was to investigate the effects of tezosentan, a non-selective ETA and ETB receptor antagonist, in LPS challenged rats with cirrhosis. Methods: Rats with cirrhosis received LPS and then tezosentan or placebo one hour later. Four hours after LPS administration, rats were killed to measure serum transaminase activity and plasma tumour necrosis factor α (TNF-α) levels. Hepatic inducible nitric oxide synthase (iNOS), myeloperoxidase (MPO), a marker of neutrophil infiltration, and cyclooxygenase (COX)-2 expression were also measured. Results: LPS administration significantly decreased arterial pressure and significantly increased plasma endothelin levels. Following LPS and tezosentan administration, serum aspartate aminotransferase and alanine aminotransferase activities were similar to those in the control group while they were increased by more than 700% with LPS alone. Plasma TNF-α levels were significantly lower in rats receiving LPS and tezosentan (182 (38) pg/ml) compared with those receiving LPS alone (821 (212) pg/ml). Tezosentan significantly decreased hepatic MPO activity and hepatic neutrophils but had no effect on LPS induced iNOS or COX-2. Survival rate was significantly higher in rats receiving LPS plus tezosentan (80%) than in rats receiving LPS alone (50%). Conclusion: In LPS challenged cirrhotic rats, tezosentan administration prevents LPS induced liver injury by decreasing intrahepatic neutrophil infiltration. In addition, tezosentan increases survival in these rats.